Boneka Tangan untuk Meningkatkan Pengetahuan Bullying pada Siswa Kelas IV SDN Ujung Menteng 07 Pagi - Imam Afrianto; Ahmad Rifqy Ash-Shiddiqy (Universitas Mathla'ul Anwar Banten, 2020)
PUPPETS TO INCREASE KNOWLEDGE ABOUT BULYYING FOR FOURTH GRADE OF ELEMENTARY SCHOOL STUDENTS UJUNG MENTENG 07 PAGI. The purpose of this study was to develop puppets with “jangan ajak temanku” Story to increase knowledge about bullying for 4th grade of elementary school students to get an information about bullying and how to cope with it. The study was included in Research and Development (R&D) using the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) development model. The study was conducted utilizing random sampling with 59 students on preliminary study. Data collection method used an interview techniques with teacher from 4th grade, and questionnaires for students. The validation result got 88% from media expert (very feasible) and 71% from content expert (feasible). The results of the small group trial got a percentage of 86% (very feasible) In media assessment, and the achievement of instructional objectives got percentage of 83%. In conclusion the puppets with “jangan ajak temanku” Story to increase knowledge about bullying for 4th grade of elementary school students can be declared as “Very Feasible”.